Consequences of Decreased Light Harvesting Capability on Photosystem II Function in Synechocystis sp. PCC 6803 - Nagarajan, Aparna (Life (Basel), 2014)
Cyanobacteria use large pigment-protein complexes called phycobilisomes to harvest light energy primarily for photosystem II (PSII). We used a series of mutants with partial to complete reduction of phycobilisomes to examine the effects of antenna truncation on photosystem function in Synechocystis sp. PCC 6803. The antenna mutants CB, CK, and PAL expressed increasing levels of functional PSII centers to compensate for the loss of phycobilisomes, with a concomitant decrease in photosystem I (PSI). This increased PSII titer led to progressively higher oxygen evolution rates on a per chlorophyll basis. The mutants also exhibited impaired S-state transition profiles for oxygen evolution. Additionally, P700(+) re-reduction rates were impacted by antenna reduction. Thus, a decrease in antenna size resulted in overall physiological changes in light harvesting and delivery to PSII as well as changes in downstream electron transfer to PSI.